Peran Pendidikan Kemaritiman Dalam Menyongsong Era Global Kebangkitan Industri Maritim Berdasarkan Undang -Undang - Tugino, Tugino; Harini, Harini (Universitas Ivet, 2024)
Indonesia as an archipelagic country (archipelagie) and 17,000 islands, both large and small, ports as a means of transportation have a role in the narrow sense, ports play a role as a place for ships to dock as a meeting point for both sea and land transportation modes for loading and unloading. for loading and unloading activities of goods or animals and passengers to and from ships. In a broad sense, the port is the gateway to the economy. Supported by reliable human resources from the role of Maritime Education as a leader or front guard who is skilled and qualified in accordance with their field. In welcoming the era of revival of the maritime transportation industry, Law number 17 of 2008 and Law number 32 of 2014 become references sea ??transportation in response to sea transportation activities and as an archipelagic country that has vast seas and long coastlines, the maritime and maritime sectors have become very strategic, which has be become the vision and mission of development management for both provincial/district, city and central governments.